Electromagnetics for engineers - Ulaby, Fawwaz T. (Fawwaz Tayssir), 1943- (Upper Saddle River, NJ : Pearson/Prentice Hall, 2005)
Accompanying CD-ROM serves as an interactive self-study supplement to the text and includes exercises and solved problems
Includes bibliographical references (p. 389) and index
System requirements for accompanying CD-ROM: Windows: Pentium-class processor, at least 100 MHz, with 32 MBytes RAM. The CD has been tested with Windows 98, using Internet Explorer 5.5. Unix/Linux: The system should be no older than about 5 years and have at least 32 MBytes RAM. Netscape 4.7 has worked on all UNIX systems we have tried. Macintosh: PowerPC processor, at least 100 MHz, with 32 MBytes RAM. The CD has been tested on a variety of MAC platforms using Internet Explorer 5.0 and Java version MRJ 2.2.2. Adobe Acrobat reader
Keywords: Electromagnetism; Electromagnetism -- Industrial applications; Electromagnetic theory